Attachment and the Development of Moral Emotions in Children and Adolescents: A Systematic Review - Mariana Costa Martins; Ana Filipa Santos; Marília Fernandes; Manuela Veríssimo (MDPI AG, 2021)
In recent years, the development of social and moral emotions (often associated to pro-social behaviors) has become the subject of increased research interest. However, the relation between these emotions and attachment is less studied. The present systematic literature review (PROSPERO: CRD42021247210) was designed to synthesize current empirical contributions that explore the link between attachment and the development of moral emotions (e.g., empathy, sympathy, altruism, and guilt) during childhood and adolescence. Article exclusion criteria included: studies with participants not living in natural contexts (e.g., institutionalized); studies on mental illness; qualitative research; research that does not reliably evaluate attachment or moral emotions; research on intervention programs; and non-peer-reviewed articles. Only 10 studies were found eligible. Results highlight a present focus on empathy and guilt and gaps regarding sympathy and altruism. The mediator role and positive effect of emotion regulation was noted. Significant positive correlations between attachment security and guilt, shame and forgiveness were emphasized. Limitations of the eligible studies included: representativeness of the participants; causality of the results; and the validity and significance of the instruments (e.g., lack of results reported by various parties involved). The present review aims to contribute to the understanding of an empathic, healthy development, in contrast to the alienation and bullying affecting the youth's emotional, relational and academic lives.